The impact of diabetes and osteoarthritis on the occurrence of stroke, acute myocardial infarction, and heart failure among older adults with non-valvular atrial fibrillation in Hawaii: a retrospective observational cohort study - Masako Matsunaga; John J. Chen; Mayumi Jijiwa; Eunjung Lim (BMC, 2021)
Abstract Background To date, little is known about cardiovascular disease risks among older adults with non-valvular atrial fibrillation by their association with diabetes and osteoarthritis status, based on longitudinal data with substantial amounts of non-white individuals. The objective of this study was to examine the risks for three cardiovascular diseases: stroke, acute myocardial infarction (AMI), and heart failure (HF), by diabetes and osteoarthritis status among older adults with non-valvular atrial fibrillation in Hawaii. Methods We conducted a retrospective observational cohort study for older adults (65 years and older) with non-valvular atrial fibrillation using the Hawaii Medicare data 2009-2017. Their risks for the three cardiovascular diseases by diabetes and osteoarthritis status (diabetes, osteoarthritis, diabetes and osteoarthritis, and without diabetes and osteoarthritis) were examined by multivariable Cox proportional hazard regression models. Results The analysis included 19,588 beneficiaries followed up for a maximum of 3288 days (diabetes: n = 4659, osteoarthritis: n = 1978, diabetes and osteoarthritis: n = 1230, without diabetes and osteoarthritis: n = 11,721).  Among them, those diagnosed with the cardiovascular diseases were identified (stroke: diabetes n = 837, osteoarthritis n = 315, diabetes and osteoarthritis n = 184, without diabetes and osteoarthritis n = 1630)(AMI: diabetes n = 438, osteoarthritis n = 128, diabetes and osteoarthritis n = 118, without diabetes and osteoarthritis n = 603)(HF: diabetes n = 2254, osteoarthritis n = 764, diabetes and osteoarthritis n = 581, without diabetes and osteoarthritis n = 4272). After adjusting for age, sex, race/ethnicity, and other potential confounders, those with diabetes and osteoarthritis had higher risks for HF (hazard ratio: 1.21 95% confidence interval: 1.10-1.33) than those without diabetes and osteoarthritis. They also had higher risks than those with osteoarthritis for HF. Those with diabetes had higher risks for all three cardiovascular diseases than the other three groups. Conclusions Variation in cardiovascular disease risks for older adults with non-valvular atrial fibrillation in Hawaii exists with diabetes and osteoarthritis status.